Preparation of Compensation Ions Codoped SrTiO3:Pr3+ Red Phosphor with the Sol-Gel Method and Study of Its Luminescence Enhancement Mechanism. (14th December 2014) - Guo, Dan; Zhang, Xiaodong; Yun, Jiangni
Abstract : SrTiO3 :Pr 3+ is the most representative titanate matrix red phosphor for field emission display (FED). The red luminous efficiency of SrTiO3 :Pr 3+ will be greatly improved after the compensation ions codoping, so SrTiO3 :Pr 3+ red phosphor has been a research focus at home and abroad. SrTiO3 :Pr 3+, SrTiO3 :Pr 3+, Mg 2+, and SrTiO3 :Pr 3+, Al 3+ phosphors are synthesized by a new sol-gel method. Crystal structure, spectral characteristics, and luminescence enhancement mechanism of the sample were studied by XRD and PL spectra. The results showed that after co-doped, SrTiO3 :Pr 3+ phosphor is single SrTiO3 cubic phase, the main emission front is located at 614 nm, corresponding to Pr 3+ ions 1D 2 → 3H 4 transition emission. SrTiO3 :Pr 3+, Mg 2+ and SrTiO3 :Pr 3+, Al 3+ phosphor luminescence intensity is enhanced, but the main luminescence mechanism is not changed. Acceptor impurity x = Mg 2+, Al 3+ will replace Ti bit after being doped into the crystal lattice to form X Ti - charge compensation corresponding defect centers Pr Sr + to reduce the demand of Sr 2+ or Ti 3+ vacancy. While Sr-doped Pr will make lattice distortion and transition energy of 4f-5d is very sensitive to crystal electric field changes around Pr atom. Doping different impurities will make electric field distribution around the icon have a different change. It increases energy transfer of 4f-5d transition and improves the luminous intensity of SrTiO3 :Pr 3+ red phosphor.